Food versus wildlife: Will biodiversity hotspots benefit from healthier diets?. Issue 6 (13th March 2022) - Rasche, Livia; Habel, Jan C.; Stork, Nigel; Schmid, Erwin; Schneider, Uwe A.
Abstract: Aims: Terrestrial biodiversity is threatened by land use change. Modelling suggests that the remaining, potentially arable areas of natural intact vegetation (rNIV) of 9 of 35 global biodiversity hotspots may be converted to agriculture by 2050, committing their endemic species to extinction. Studies have shown that if the global population adopted a healthy, mostly plant based diet, agricultural area expansion can be reduced. We want to examine to what degree this applies to the regions covered by biodiversity hotspots. Location: Global. Time period: 2020–2050. Major taxa studied: No particular taxa. Methods: For every biodiversity hotspot, we simulate climate change impacts on agricultural productivity, and estimate food demand shifts from 2010 to 2050 by processing population and income growth projections. We quantify the net change in rNIV by 2050 in all hotspots by calculating the agricultural area necessary to meet the food demand under a business as usual, a healthy diet, a healthy diet plus agricultural intensification, and a healthy diet plus agricultural intensification plus crop change scenario. Results: In the healthy diet scenario, the rNIV of 16–21 hotspots can be preserved entirely, but 5–6 hotspots in less developed regions may lose all rNIV to agricultural area expansion. In these regions, a healthy diet implies an increase in consumed calories and no change in the already high share of plant‐based calories. When combined with agricultural intensification, these hotspots will still lose 7%–92% of rNIV. Only an additional change in crop mix patterns may preserve all. Main conclusions: While a change in dietary habits may be sufficient for preservation of rNIV in many hotspot regions, a healthy diet actually puts more pressure on rNIV in other hotspot regions. Intensifying agriculture and optimizing crop selection should be priorities in those regions to mitigate the expected loss of rNIV to agricultural expansion.